2021
DOI: 10.3390/ijms22126287
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana G3BP Ortholog Rescues Mammalian Stress Granule Phenotype across Kingdoms

Abstract: Stress granules (SGs) are dynamic RNA–protein complexes localized in the cytoplasm that rapidly form under stress conditions and disperse when normal conditions are restored. The formation of SGs depends on the Ras-GAP SH3 domain-binding protein (G3BP). Formations, interactions and functions of plant and human SGs are strikingly similar, suggesting a conserved mechanism. However, functional analyses of plant G3BPs are missing. Thus, members of the Arabidopsis thaliana G3BP (AtG3BP) protein family were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…G3BPs are also well-known to play an important role in viral immunity, since SGs are the primary target of virus infection [12]. In the model plant Arabidopsis, seven G3BP-like proteins have been identified with both the NTF2 and RRM domains [13,14]. This also shows that all plant G3BPs, like human and animal G3BPs, promote SG formation.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…G3BPs are also well-known to play an important role in viral immunity, since SGs are the primary target of virus infection [12]. In the model plant Arabidopsis, seven G3BP-like proteins have been identified with both the NTF2 and RRM domains [13,14]. This also shows that all plant G3BPs, like human and animal G3BPs, promote SG formation.…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies have suggested functional similarities between human and Arabidopsis G3BPs [14,15]. To gain insights into the expression patterns of G3BPs in Arabidopsis, we analyzed the RNA-seq data from the intergraded Arabidopsis RNA-seq Database (http://ipf.…”
Section: Expressional Patterns and Subcellular Localization Of G3bps ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It destabilises the messenger through the interaction with YTHDF2 that transfers it to repressive condensates, such as P-bodies and stress granules (SGs) [17]. Two research papers in this Special Issue focus on SGs, their conserved components and some new, unexpected properties [1,2]. Stress granules typically form, as the name suggests, under stress conditions, which activate eIF2α kinases that phosphorylate, and thereby inactivate, the initiation factor eIF2.…”
mentioning
confidence: 99%
“…As it is often the case with plants, the A. thaliana genome encodes as many as seven G3BP homologues, raising questions of their respective molecular roles and their involvement in SG formation. An elegant study by Reuper et al in this Special Issue leverages trans-kingdom functional complementation to single out two plant G3BP-like proteins that can rescue sodium arsenite-induced SG formation in human cells that lack both native G3BP homologues [1]. Even more strikingly, domain swaps, in which the RG/RGG domains of the plant proteins were grafted on the human G3BP-1 scaffold, all turned out to be proficient in SG formation.…”
mentioning
confidence: 99%